Evaluation of cooling performance of a novel dual-purpose solar thermal collector through numerical simulations. (5th March 2022) - Miao, Rui; Hu, Xiaoou; Yu, Yao; Zhang, Yan; Wood, Mark; Olson, Gaylord; Yang, Huojun
Highlights: Develop a new solar thermal collector that allows heat and cold collection. Cooling capacities were estimated through numerical simulations using COMSOL. The average cooling capacity is 28.5∼262.4 W/m 2 across the US climates. Higher cooling capacities are achievable under high wind/rich precipitation. Abstract: Flat Plate Solar Collector (FPSC) has been popularly used in the US and is typically covered on top with a single-pane glass, known as glazed FPSC, which, however, can only be used for heat collection. This paper aims to develop an innovative dual-purpose solar thermal collector that allows heat collection during daytime and cold collection during night. It was developed from a conventional glazed FPSC by using a double-pane cover on the top that allows water or other liquid flowing in the gap between the two panes to accomplish heat removal, while its heat-collection function will still be retained, which is accomplished similarly to a conventional FPSC through the copper tubes embedded in the absorber plate underneath. Specifically, the cooling performance of the developed collector was evaluated in this study through simulations carried out in the environment of COMSOL Multiphysics. The results show that the average cold collection capacity of the developed collector is between 28.5 and 262.4 W/m 2 when used in various climates across the US, e.g., from the hot (e.g., Miami) to cold (e.g., Anchorage) climate zones, respectively, as the result of both convective and radiative cooling during summer nights. This type of collector is more suitable for use in commercial buildings that have a large amount of internal heat gains and located in cool/cold climate cities or regions (such as Climate Zone 5, 6, 7, and 8) with high wind and/or rich precipitation (e.g., Kansas City or Chicago) for space cooling.